ROBERT BROWNING AND HIS DRAMATIC MONOLOGUES AS A BRIDGE BETWEEN EXPERIMENT AND TRADITION (Journal of Contemporary Philology, 2019)
In our paper we shall give a short overview of the historical development of the dramatic monologue, a hybrid genre between poetry and drama in which Robert Browning played a crucial role to develop. It resulted directly from the crisis of poetry and its inability to deal with the challenges caused by the tectonic changes in all areas of 19th century society. We shall discuss the main structural and thematic features of the dramatic monologue, as well as the importance of the dramatis personae as the narrator and its role in incorporating polyphony in the monological structure of poetry. Finally, we shall also look at the dramatic monologue as a genre providing Browning the platform to imitate and incorporate the myriad voices and discourses present in British society. As a specific example for this approach, we shall analyze the dramatic monologue Child Roland to the Dark Tower Came in order to more concretely present the poetics and narrative strategies of Browning.
Keywords: Robert Browning; poetry; Victorian literature; dramatic monologue; dramatis personae